A Case Study of Stress-Induced Alopecia Areata Treated with Hominis Placenta Pharmacopunture - Yeon Woo Song; Seo Young Kang; Chae Won Kang; Seok Hee Kim; Kyung Jin Lee; Yeon Ju Kim; Jong Uk Kim; Tae Han Yook (Korean Pharmacopuncture Institute, 2024)
The purpose of this study is to report the clinical application of Hominis Placenta Pharmacopunture for Alopecia areata. Patient was diagnosed as stress-induced Alopecia areata 1 years ago. To reduce symptom, we treated a patient 8 times using Hominis Placenta Pharmacopunture. Hominis Placenta was injected subcutaneously into the lesion of head scalp alopecia. According to photographs, the lesion had been replaced with new terminal hair and the size of the lesion had decreased. This case has shown that stress-induced Alopecia areata patient could be treated by Hominis Placenta Pharmacopunture.